2009
DOI: 10.5539/jas.v1n1p3
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Dried Distillers Grain as a Fertilizer Source for Corn

Abstract: Increased ethanol production may result in excessive dried distillers grains (DDGs) that could be utilized as a fertilizer source for corn (Zea mays L.). Research was conducted to evaluate the effects of 1) DDG rates on weed suppression, changes in soil properties, and differences in grain yield and quality and 2) DDGs, polymer-coated urea (PCU), and anhydrous ammonia (AA) fertilizer sources on grain yield and quality. DDGs had a total N-P-K composition of 38.2-6.9-11.5 g kg -1 , respectively. There was no cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…In addition to N, P and K content of biofuel byproducts is also of great value to growers. As reported by Nelson et al (2009), the N:P of the DDGS used in the study (5.5:1) was comparable to corn uptake ratios (5.9:1), suggesting that DDGS and other biofuel byproducts with similar N:P ratios could meet both the N and P needs of a crop when applied on a N basis without over-or under-applying P. In 2008, many U.S. growers were unable to afford P or K chemical fertilizers. Based on values listed in table 2, biofuel byproducts may be a viable option for these growers in the future if and when P and K fertilizer prices increase beyond what a grower can afford to pay.…”
Section: Plant Nutrient Compositionsupporting
confidence: 67%
See 1 more Smart Citation
“…In addition to N, P and K content of biofuel byproducts is also of great value to growers. As reported by Nelson et al (2009), the N:P of the DDGS used in the study (5.5:1) was comparable to corn uptake ratios (5.9:1), suggesting that DDGS and other biofuel byproducts with similar N:P ratios could meet both the N and P needs of a crop when applied on a N basis without over-or under-applying P. In 2008, many U.S. growers were unable to afford P or K chemical fertilizers. Based on values listed in table 2, biofuel byproducts may be a viable option for these growers in the future if and when P and K fertilizer prices increase beyond what a grower can afford to pay.…”
Section: Plant Nutrient Compositionsupporting
confidence: 67%
“…Nelson et al (2009) investigated three field application rates of DDGS in comparison to a slow-release poly coated urea (PCU) and anhydrous ammonia on a corn grain crop. Using application rates of 0, 1.2, 2.4, and 3.6 tonne DDGS ha -1 (or 0, 46, 92, and 138 kg N ha -1 ), Nelson et al (2009) showed a grain yield increase of 1.41 and 1.56 kg grain ha -1 for every kg ha -1 of DDGS applied in medium and high yielding environments. Balesh et al (2005) applied mustard meals as a fertilizer for tef at three application rates of 0.24, 0.38, and 0.51 tonne meal ha -1 (or 15, 23, and 31 kg N ha -1 ).…”
Section: Biofuel Byproducts As Fertilizers -Research Effortsmentioning
confidence: 99%
“…Soil texture was 13% sand, 62% silt, and 25% clay. Soil test values for P and K at this site [26] were in the medium to very-high range, based on Missouri soil test interpretations [27] and required no additional fertilizer inputs for these experiments. Field information and selected management practices are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…However, if contaminated corn is used as the feedstock, aflatoxins can be retained within the DDG [11]. This causes the DDG to be unsalable if addition to feedstuffs causes the combined product to exceed FDA limits, leading to a profit loss for the ethanol distillery [12].…”
Section: Introductionmentioning
confidence: 99%